SABUN CAIR EKONOMIS DENGAN PEMANFAATAN LIMBAH MINYAK JELANTAH - Indica Septriyanti; Aisyah Meisya Putri; Herman Herman; Yelfira Sari (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2021)
Reducing Environmental pollution from household products that are used continuously, Processing waste cooking oil waste can be used to make innovations that benefit the community. Cooking oil that is used in excess of its use is called used cooking oil which is not well consumed by the body and has a negative impact on soil and air pollution. Processing of used cooking oil can be made as soap, one of which is liquid soap. Liquid soap is cleaner and more effective soap in packaging and usage.